Application of Propensity-Score Matching in Four Leading Medical Journals. Issue 2 (March 2015) - Wu, Shunquan; Ding, Yingying; Wu, Fuquan; Hou, Jun; Mao, Panyong
<x xml:space="preserve">Abstract</x> Supplemental Digital Content is available in the text.